Solid-state NMR in drug design and discovery for membrane-embedded targets. - Watts, A (2005)
Observing drugs and ligands at their site of action in membrane proteins is now possible through the use of a development in biomolecular NMR spectroscopy known as solid-state NMR. Even large, functionally active complexes are being examined using this method, with structural details being resolved at super-high subnanometre resolution. This is supplemented by detailed dynamic and electronic information about the surrounding ligand environment, and gives surprising new insights into the way in which ligands bind, which can aid drug design.